MENUMBUHKAN SIKAP SOSIAL DAN SPIRITUAL SISWA DI SEKOLAH - Mohamad Aso Samsudin; Ukhtul Iffah (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2020)
Criticism of the world of education about the intellectual abilities of students that are not balanced with the attitude they have is never lost. Every time an immoral student act occurs, the glory of education is tarnished. In this connection, education is no longer the right place to foster moral and religious students. So, it is necessary to motivate students to be motivated to do the best. Various thoughts are offered to motivate students in kindness. One of them is the fostering of spiritual and social attitudes through schools, either through the intracuricular door or the extracurricular door. Within the two entrances for developing this attitude there are various activities such as Islamic education learning and guidance-counseling in intracuricular activities, and Red Cross Teenagers, Scouts, and Rohis in extracurricular activities. In addition to the forms of attitude building activities, strategies and ways of fostering attitudes can also be offered in these types of activities.